A post-synthetically reduced borane-functionalised metal–organic framework with oxidation-inhibiting reactivity. Issue 32 (30th July 2020) - Ablott, Timothy A.; Telfer, Shane G.; Richardson, Christopher
Abstract : Highly porous boron-loaded MOFs with novel auto-oxidation inhibiting reactivity are achieved via post-synthetic ketone reduction and alcohol reactions with H3 B·THF. Abstract : The first post-synthetic reduction of a ketone-containing metal–organic framework (MOF) is reported. The borane tetrahydrofuran complex (H3 B·THF) quantitatively reduced a ketone functional group in a porous zinc(ii ) IRMOF-9 scaffold at room temperature. Single crystal X-ray diffraction studies established that the crystallinity and interpenetration mode of the framework are preserved during reduction. Boron remains bound in the framework and can be removed via mild acid treatment to yield a MOF with identical properties to that prepared by direct synthesis. The boron-functionalised MOF was unable to reduce benzaldehyde but instead was found to inhibit benzaldehyde autooxidation.